Corporate social responsibility and shareholder's value: an empirical analysis - Leonardo Becchetti; Rocco Ciciretti; Iftekhar Hasan (Bank of Finland, 2009)
In today s global economy, corporate social responsibility (CSR) is a core component of corporate strategy. Due in part to financial scandals, losses, and the diminished reputation of the affected listed companies, CRS is emerging as a crucial instrument for minimizing conflicts with stakeholders. While corporations are busy adopting and enhancing CSR practices, there is (beyond a very few notable exceptions) no established empirical research on its impact and relevance for the capital market. Our paper investigates this issue by tracing market reactions to corporate entry into and exit from the Domini 400 Social Index (a recognized CSR benchmark) between 1990 and 2004. Our paper highlights two main findings: i) a significant upward trend in absolute values of abnormal returns, irrespective of the event (entry/exit vis-à-vis the index) type; and ii) a significant negative effect on abnormal returns after announcement from the Domini index. The latter effect continues to persist even after controlling for concurring financial distress shocks and stock market seasonality.
URN:NBN:fi:bof-20140807195
Keywords: 330